In situ sludge reduction induced by graphene oxide: Mechanistic insights into metabolic uncoupling, maintenance energy and cryptic growth - Yaodong Wu; Yiqi Sun; Rui Yu; Yanan Cui; Fan Yang; Jun Li; Zehao Zhang (Bioresource Technology, 2026)

Oral or nasal immunization of piglets with porcine epidemic diarrhea virus (PEDV) S1 protein bacterial-like particles induces robust intestinal mucosal immune responses and provides reliable protection - Kai Su; Jing Ren; Yawen Wang; Chen Yuan; Yanan Zhang; Tingli Fan; Zelin Liu; Tairan Sun; Liu Yang; Xiaobo Wang; Qinye Song (Veterinary Microbiology, 2026)

Effects of different morphologies of CeOₓ on the unsaturated Mn/Co defects of MnOₓ/CoOₓ catalysts for highly active photothermocatalysis of acetone and NO - Siqi Jiang; Sihan Li; Yinming Fan; Yanping Zhang; Shengpeng Mo; Lei Liao; Yanan Zhang; Xiaobin Zhou; Zongqiang Zhu (Journal of Environmental Chemical Engineering, 2026)

A comprehensive review on PIM-1 membranes for enhanced CO2 separation: strategies for CO2 transport enhancement - Shaohan Lian; Jiangxue Fan; Xiangyun Meng; Boyuan Fu; Siqi Zhang; Jing Han; Tianyang Zhao; Yanan Guan; Erhong Duan; Chunfeng Song (Environmental Research, 2026)

Multi-dimensional metabolic engineering and enzyme engineering in Escherichia coli for highly efficient biosynthesis of 2,5-furandicarboxylic acid - Yanan Cui; Peiyi Zhang; Renjie Miao; Mengqi Zhao; Liqiang Fan; Xu Li; Yongjun Qiu; Chen Deng; Liming Zhao (Bioresource Technology, 2026)

Mixed-dimensional COF membrane towards fast organic solvent nanofiltration - Fenglong Dai; Tingyuan Wang; Yanan Liu; Xiaocui Wei; Fu Zhao; Enshen Shi; Yigui Du; Chunjia Wang; Shijie Liu; Chunyang Fan; Yuhan Wang; Zhongyi Jiang (Chemical Engineering Journal, 2026)

TianGong database—an open-source, ILCD entry-level life cycle unit process database of china - Ming Xu; Weiqiang Chen; Yutao Wang; Lei Shi; Zhi Cao; Huimin Chang; Chang Chen; Xiangbin Ding; Jianwei Du; Huabo Duan; Kai Fang; Cuiyang Feng; et al. (Journal of Industrial Ecology, 2026)

Harnessing spatial effects to modulate electron donation/withdrawal at Fe single-atom sites for water purification - Yafei Fan; Haoru Song; Feifei Wang; Dezhi Kong; Menghui Chu; Yanan Zhou; Guanyun Zhang; Chen-Ho Tung; Mingyang Xing; Yifeng Wang (Science Bulletin, 2026)

Antibody-drug conjugates in breast cancer brain and leptomeningeal metastases: mechanistic insights and therapeutic progress - Hanqi Zhang; Yaqing Qin; Hanzhi Chu; Yidan Fan; Jiayi Tang; Wei Deng; Xinhao Zheng; Ze Yuan; Yutian Zou; Yanan Kong (Cancer and Metastasis Reviews, 2026)

Temperature-driven competitive dominance of Ulva prolifera in the Yellow Sea green tides revealed by multi-species comparative study - Weifan Yang; Shanying Tong; Dong Xu; Bingkun Wang; Xintong Huang; Yanmin Sun; Haoming Sun; Yanan Zhang; Yapeng Wang; Fan Yang; Yingxia Li; Xiaoli Liu; et al. (Marine Environmental Research, 2026)

Synergy between acidity and Pt in Pt/HY zeolite for boosting the hydrocracking of polyethylene to C5-C7 liquid fuels - Wenshang Zhang; Yanan Huang; Jingjing Fan; Guoqiang Shen; Hao Chen (Journal of Environmental Sciences, 2026)

Low-barrier interface via noble metal induction for external energy-free ppb-level room-temperature formaldehyde sensing - Ziming Yang; Jiangnan Chang; Ying Qiao; Sitao Lv; Leqi Zhang; Yifei Fan; You Wu; Ruofei Lu; Hao Li; Yanan Guo; Patrick J. French; Jun Yin; et al. (Chemical Engineering Journal, 2026)

Synergistic enhancement of polyvinyl alcohol coating via montmorillonite reinforcement and chemical cross-linking for high-barrier food packaging - Qingmei Zhu; Jiji Fan; Yanan Bu; Xiuqiong Chen; Huiqiong Yan; Qiang Lin (Applied Clay Science, 2026)

Exploring the Associations Between the Gut Microbiome and Mating Behavior in Free-ranging Male Tibetan Macaques (Macaca thibetana) - Fan Zhang; Chuanpeng Bao; Dongxin Yang; Yue Ling; Ximeng Zhu; Yanan Wu; Yuhao Chen; Xiaojuan Xu; Binghua Sun (International Journal of Primatology, 2026)

Linking long-term habitat suitability dynamics to management effectiveness for waterbirds in the yellow river delta - Rongji Cheng; Zhonghua Ning; Xiaoqian Li; Longmian Wang; Mingxiang Zhang; Yanan Wu; Yidan Sun; Jingwen Wang; Fan Zhang; Zhenming Zhang; Jiakai Liu (Journal of Environmental Sciences, 2026)

Parental DEHP exposure induces sex-specific reproductive toxicity in zebrafish and behavioral deficits in unexposed offspring - Yanan Sun; Yuqing Fan; Yao Dang; Ping Ding; Xin Li; Gang Li; Haojie Luo; Jianliang Zhao; Guocheng Hu (Environmental Pollution, 2026)

Multi-tissue transcriptomics and metabolomics analyses uncover gonadal developmental disorders and metabolic homeostasis imbalances in male Penaeus vannamei following insulin receptor interference - Yanan Yin; Haitao Fan; Ruiyan Xing; Jiajie Xu; Lefei Jiao (Aquaculture, 2026)

Plasma untargeted lipidomics based on UHPLC-Orbitrap-MS reveals potential biomarkers and the pathogenesis involved in Mycoplasma bovis pneumonia - Fei Yang; Fan Liu; Yufei Zhai; Shenghu He; Mengmeng Yang; Ke Li; Yanan Guo (Veterinary Microbiology, 2026)

Maternal-fetal transfer of emerging bisphenols: Exposure profile and potential link to latrogenic preterm birth - Zhenni Zhu; Dongying Zhang; Ruihong Zhu; Zixiong Tang; Shuai Li; Chunhong Jia; Zhiwen Su; Yanan Pan; Renli Yin; Fan Wu; Adela Jing Li; Rongliang Qiu (Environmental Toxicology and Pharmacology, 2026)

Changes in root morphological traits, soil properties, and infiltration characteristics following the conversion of native forests to Carya cathayensis plantations in the Dabie mountainuous area, China - Yun Zhu; Chunqiang Zhang; Yunpeng Wang; Hongda Zhang; Lei Sun; Xia Liu; Yanan Wang; Abdul Hakim Jamshidi; Zhaofei Fan (European Journal of Forest Research, 2026)

The regulatory effect of environmental factors on green tide blooms in the Yellow Sea: A spatio-temporal downscaling numerical reconstruction method - Liqiang Fan; Yanan Chen; Xianli Song; Jing Zhao; Xiaoyong Shi; Keqiang Li; Xiulin Wang (Marine Environmental Research, 2026)

Using DNA metabarcoding to monitor key factors affecting the fungal community in Licorice: collection site, processing method, and storage condition - Yanan Xu; Junrong Wang; Chune Fan; Huilin Yuan; Meihua Yang; Jianping Han; Xiaohui Pang (Food Research International, 2026)

Isolating a novel quorum quenching strain based on carbon source adaptability for bioaugmentation under different carbon source conditions - Jun Li; Yanan Cui; Fan Yang; Yanxue Pei; Muchen Yin; Chaofan Xie; Yaodong Wu (Bioresource Technology, 2026)

Sub-monthly features of atmospheric circulations leading to June extreme precipitation in Southwest Zhejiang Province of China - Peijun Zhu; Renguang Wu; Chengyan Mao; Jianjiang Wang; Yanan Liu; Fan Ping; Panxi Dai (Theoretical and Applied Climatology, 2026)

Single-cell omics analysis reveals tumor microenvironment rewiring after arsenic trioxide therapy in acute promyelocytic leukemia - Gang Xu; Jiyu Guo; Shengjin Fan; Si Li; Ting Qiu; Zefeng Chen; Yanan Liu; Luan Wen; Chongwen Lv; Yanan Jiang; Huitao Fan; Juan Xu; et al. (Science Bulletin, 2026)

Constructed NiS-Mn2SnS4/g-C3N4 dual-stage type-II heterojunction with high-specific-surface-area for synergistically enhanced photocatalytic hydrogen production performance - Jing Fan; Yanan Yang; Jie Liu; Qi Qi; Fenhong Song (Fuel, 2026)

Synergistic enhancement of CO2 capture via a dual-activator strategy: Mechanism insights into tertiary amine-boosted absorption and alcohol-facilitated regeneration - Xiaobin Zhou; Ting Zou; Yunqiong Tang; Shengpeng Mo; Yinming Fan; Bihong Lv; Yanan Zhang; Dunqiu Wang; Yinian Zhu; Zongqiang Zhu; Guohua Jing (Chemical Engineering Journal, 2026)

Dual-function trehalose transporters link metabolic adaptation to diapause plasticity and fecundity in Trichogramma dendrolimi (Hymenoptera: Trichogrammatidae) - Xue Zhang; Xiaoyang Song; Meixin Zheng; Jiaqing Guo; Yanan Fan; Jianbo Huang; Qianyu Zhang; Junjie Zhang; Changchun Ruan (Journal of Insect Physiology, 2026)

Pt-Cu dual-atom pairs-triggering intermediate activation on single-atom catalysts for enhanced photothermal catalytic VOCs oxidation in cooking oil fumes - Yanan Zhang; Xiaoxue Song; Zichao Chen; Yinming Fan; Xiaobin Zhou; Zongqiang Zhu; Qinglin Xie; Shengpeng Mo; Bing Li; Jianjun Chen; Junhua Li (Journal of Hazardous Materials, 2026)

Synergy of nanoclusters/single atoms regulates sustainable oxidation pathways for self-motivated Fenton-like processes - Mengyao Fan; Yanwei Li; Tianran Zhang; Zhaokai Gao; Yan Wu; Yanan Shang; Zongchao Huo; Xuemin Zhao; Yue Gao; Longlong Geng; Xing Xu (Water Research, 2025)

Preclinical safety and toxicokinetic evaluation of TJ0113, a first-in-class mitophagy inducer for Parkinson's disease - Yanan Tian; Fengqi Wang; Jikai Shen; Ruiqi Zhang; Qianwen Chen; Le Xu; Dong Liu; Mengyang Fan; Zhen Tian; Xufeng Cen; Xiaoyan Xu; Hongguang Xia (Toxicology and Applied Pharmacology, 2025)

A two-stage ensemble evolutionary algorithm for constrained multi-objective optimization - Sri Srinivasa Raju Modampuri; Jiahao Fan; Yanan Sun (Swarm and Evolutionary Computation, 2025)

The dual role of water in CO2 capture by a novel 2-(ethylamino)ethanol-based non-aqueous phase-change absorbent: A net positive effect - Dunqiu Wang; Jingfeng Shen; Dan Wang; Yinming Fan; Shengpeng Mo; Bihong Lv; Yanan Zhang; Yinian Zhu; Zongqiang Zhu; Mi Feng; Xiaobin Zhou; Guohua Jing (Chemical Engineering Journal, 2025)

ILP/TORC1 nutrient-sensing pathways mediated leucine regulation on the vitellogenin synthesis to promote ovary development of Litopenaeus vannamei - Yanan Yin; Xin Zhang; Haitao Fan; Lefei Jiao (Animal Feed Science and Technology, 2025)

A nutrient–microalgae– Ulva prolifera biological model: Key factors and processes in the control of green tides in the Yellow Sea - Yanan Chen; Xianli Song; Liqiang Fan; Kan Chen; Keqiang Li; Xiulin Wang (Limnology and Oceanography, 2025)
The Yellow Sea has experienced the world's largest green tide of Ulva prolifera in each of the last 18 yr. Limited understanding of the mechanisms controlling U. prolifera growth and death complicates mitigation efforts. Focusing on the crucial factors and processes affecting U. prolifera blooms, we constructed a nutrient–microalgae– U. prolifera –detritus (NmiAUD) model based on the results of field microcosm experiments. The NmiAUD model characterized the growth and death processes of U. prolifera and the nitrogen and phosphorus biogeochemical processes in the Yellow Sea with good reliability. Parameter sensitivity, process correlation analysis, and numerical experiments were used to identify the most critical factors and processes. Nutrient concentrations were the most important factors controlling the growth and death of U. prolifera , followed by seawater temperature, initial biomass, and photosynthetically active radiation, with contribution rates of 55.1%, 23.9%, 16.0%, and 5.0%, respectively. Nitrogen was more important than phosphorus, with nitrate‐nitrogen accounting for 29.9%, followed by ammonium‐nitrogen (26.3%), dissolved organic nitrogen (19.9%), phosphate‐phosphorus (17.1%), and dissolved organic phosphorus (6.8%). The key processes comprised nutrient absorption, nutrient assimilation, degradation, detritus generation, dissolved organic matter mineralization, and detritus decomposition. Microalgae, which show high rates of growth, mortality, and nutrient uptake, are indicated to have a competitive advantage in the higher nutrient conditions in the South Yellow Sea, whereas U. prolifera is better adapted to the lower nutrient conditions in the North Yellow Sea. This study provides a scientific basis for the prevention and control of green tides.

A highly Swellable hydrogel encapsulating Ginsenoside Rh4 for obesity regulation - Yanan Liu; Haixia Yang; Daidi Fan; Jianjun Deng (Food Research International, 2025)

Fabrication of nonionic surfactant modified montmorillonite for alginate/organo-montmorillonite composite fibers based hydrophobic pharmaceutical formulations - Yanan Bu; Xiuqiong Chen; Ting Wu; Jiji Fan; Haizhen Dai; Huiqiong Yan; Qiang Lin (Applied Clay Science, 2025)

Mapping for Larimichthys crocea Aquaculture Information with Multi-Source Remote Sensing Data Based on Segment Anything Model - Xirui Xu; Ke Nie; Sanling Yuan; Wei Fan; Yanan Lu; Fei Wang (Fishes, 2025)
Monitoring Larimichthys crocea aquaculture in a low-cost, efficient and flexible manner with remote sensing data is crucial for the optimal management and the sustainable development of aquaculture industry and aquaculture industry intelligent fisheries. An innovative automated framework, based on the Segment Anything Model (SAM) and multi-source high-resolution remote sensing image data, is proposed for high-precision aquaculture facility extraction and overcomes the problems of low efficiency and limited accuracy in traditional manual inspection methods. The research method includes systematic optimization of SAM segmentation parameters for different data sources and strict evaluation of model performance at multiple spatial resolutions. Additionally, the impact of different spectral band combinations on the segmentation effect is systematically analyzed. Experimental results demonstrate a significant correlation between resolution and accuracy, with UAV-derived imagery achieving exceptional segmentation accuracy (97.71%), followed by Jilin-1 (91.64%) and Sentinel-2 (72.93%) data. Notably, the NIR-Blue-Red band combination exhibited superior performance in delineating aquaculture infrastructure, suggesting its optimal utility for such applications. A robust and scalable solution for automatically extracting facilities is established, which offers significant insights for extending SAM’s capabilities to broader remote sensing applications within marine resource assessment domains.

Deciphering the preservative effects of protamine from Xinjiang Coregonus peled on grass carp (Ctenopharyngodon idellus) fillets during refrigerated storage: a perspective from the microbiome - Rong Zhang; Yanan Gao; Xiaoji Fan; Song Zhu; Tingzhang Wang; Lili Gao; Xueqin Zhao; Zhuang Ma; Yiling Fan; Dan Jiang; Shuyan Liu (International Journal of Food Microbiology, 2025)

Boron isotope evidence for Ordovician-Silurian Transition postglacial marginal marine salinity with implications for redox conditions and biotic recovery - Jingyu Zhang; Wei Wei; Jun Shen; Jingbo Nan; Yi Zhong; Xiaojie Fan; Yanan Zhang; Qingsong Liu; Lin Chen; Leslie J. Robbins; Kurt O. Konhauser (Chemical Geology, 2025)

The Adhesion Characteristics of Fouling Organism on Two Kinds of Mesh Coat - Lei Li; Jinmeng Bao; Dagui Liao; Yanan Wei; Cong Yan; Xiaoxu Fan; Shen Lin; Dan Liu; Wei Tian; Yanming Sui; Mei Jiang (Thalassas: An International Journal of Marine Sciences, 2025)

The Yr9 gene encoding a CC-NBS-LRR protein in the 1RS-1BL translocation confers wheat stripe rust resistance - Chunhui Wang; Yanan Chang; Mian Wang; Jing Wang; Chang Liu; Chaolan Fan; Congyang Yi; Chen Zhou; Jing Yuan; Wuyun Yang; Dengcai Liu; Tao Wang; et al. (Science China Life Sciences, 2025)

Decomposition of Nelumbo nucifera Litters with Three Initial Biomasses Significantly Affected the Microbial Community and Assembly in Sediment - Fan Wu; Deyou Feng; Yanan Li; Xin Liu; Xiaohong Zhou; Sisi Xiao; Qingjie Xie (Current Microbiology, 2025)

Adjusting Co ratios to control the unsaturated Mn defects in nanostick-assembled CoOx@MnOx double layered sphere catalysts for highly active photothermocatalysis of acetone/ethyl acetate and NO without ammonia - Yinming Fan; Weihan Wu; Yanping Zhang; Yinian Zhu; Shengpeng Mo; Lei Liao; Mingming Fu; Yanan Zhang; Xiaobin Zhou; Zongqiang Zhu (Journal of Environmental Chemical Engineering, 2025)

Pathways and impacts of ENSO-induced oceanic variability in the southern Indian Ocean investigated with high-resolution model simulations - Yanan Zhu; Yuanlong Li; Yilong Lyu; Fan Wang (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

High-fidelity 3D reconstruction of peach orchards using a 3DGS-Ag model - Yanan Chen; Ke Xiao; Guandong Gao; Fan Zhang (Computers and Electronics in Agriculture, 2025)

Contriving molecular configuration to realize a bidirectionally stable quasi-solid polymer electrolyte for high-voltage Li metal batteries - Silin Chen; Shunchao Ma; Yu Zhang; Yanan Li; Yutong Yang; Shuainan Wang; Jianli Cao; Siqi Fan; Liqun Sun; Yulong Liu; Lina Cong; Haiming Xie (Chemical Engineering Journal, 2025)

Regulated synthesis of 3D Mn2O3 hollow microspheres derived from Mn-BTC for concentrating solar-driven photothermal ethyl acetate oxidation - Zichao Chen; Jiaxi Zheng; Shengmei Huang; Lili Huang; Yinming Fan; Xiaobin Zhou; Yanan Zhang; Zongqiang Zhu; Qinglin Xie; Shengpeng Mo; Daiqi Ye (Journal of Environmental Chemical Engineering, 2025)

An accuracy-enhanced risk assessment framework for compound flood peak–volume effects using a mixed copula-probabilistic approach: a case study of the Yangtze River Basin, China - Hai Sun; Zhimin Li; Yanan Chu; Xuejing Ruan; Jun Wang; Chao Fan (Natural Hazards, 2025)

Abdominal LIPUS Stimulation Prevents Cognitive Decline in Hind Limb Unloaded Mice by Regulating Gut Microbiota - Yumei Zheng; Yanan Yu; Mengyao Chen; Huiyuan Zhang; Wanzhao Wang; Xiushan Fan; Lijun Sun; Liang Tang; Dean Ta (Molecular Neurobiology, 2025)

Warming-Induced Increase in Flooding in the Taklimakan Desert - Yanan Su; Xin Wang; Xiangjun Luo; Shengqian Chen; Yaqi Chen; Fan Yang; Jiaqiang Lei; Fahu Chen (Journal of Earth Science, 2025)

Economic viability-driven biorefinery site selection for cellulosic biofuel production in Western Canada - Huanhuan Wang; Feng Qiu; Xiaoli Fan; Yanan Zheng; Mauricio Diego Soria Rodriguez (Biosystems Engineering, 2025)

Matrix stiffening induces hepatocyte functional impairment and DNA damage via the Piezo1‒ERK1/2 signaling pathway - Yanan Fan; Caizhelin An; Zhihui Wang; Jia Luo; Wenbin Wang; Qing Luo; Guanbin Song (Journal of Physiology and Biochemistry, 2025)

Cyclodextrin tuned interlayer spacing in covalent organic framework membranes for efficient dye/salt separation - Xiaocui Wei; Yanan Liu; Jianghao Huang; Zongmei Li; Fu Zhao; Zhao Zhang; Tingyuan Wang; Chunyang Fan; Yuhan Yang; Zhongyi Jiang (Desalination, 2025)

Corrigendum to “Long-term warming and acidification interaction drives plastic acclimation in the diatom Pseudo-nitzschia multiseries” [Mar. Environ. Res. 204 (2025) 106901] - Yanmin Sun; Fan Yang; Ran Duan; Dong Xu; Yanan Zhang; Chengwei Liang; Zhuonan Wang; Xintong Huang; Bingkun Wang; Yapeng Wang; Haoming Sun; Naihao Ye; et al. (Marine Environmental Research, 2025)

Long-term warming and acidification interaction drives plastic acclimation in the diatom Pseudo-nitzschia multiseries - Yanmin Sun; Fan Yang; Ran Duan; Dong Xu; Yanan Zhang; Chengwei Liang; Zhuonan Wang; Xintong Huang; Bingkun Wang; Yapeng Wang; Haoming Sun; Naihao Ye; et al. (Marine Environmental Research, 2025)

The Association Between Functional Variants in Long Non-coding RNAs and the Risk of Autism Spectrum Disorder Was Not Mediated by Gut Microbiota - Kaiheng Zhu; Xinyan Xie; Fang Hou; Yanlin Chen; Haoxue Wang; Qi Jiang; Yanan Feng; Pei Xiao; Quan Zhang; Zhen Xiang; Yixi Fan; Xufang Wu; et al. (Molecular Neurobiology, 2025)

Two distinct evolutions of extreme precipitation over central eastern China during June and July - Renguang Wu; Peijun Zhu; Panxi Dai; Fan Ping; Jianjiang Wang; Chengyan Mao; Yanan Liu (Climate Dynamics, 2025)

Differences in glycogen and lipid accumulation and mobilization during ovarian maturation in female Litopenaeus vannamei - Yanan Yin; Haitao Fan; Xin Zhang; Zhangyi Zheng; Jiajie Xu; Tinghong Ming; Fei Kong; Lefei Jiao (Aquaculture International, 2025)

Fungal communities in three root herbs: Insights and implications - Yanan Xu; Chune Fan; Huilin Yuan; Yufeng Li; Jianping Han; Meihua Yang; Xiaohui Pang (Journal of Applied Research on Medicinal and Aromatic Plants, 2024)

Comprehensive foodomics analysis reveals key lipids affect aroma generation in beef - Longzhu Zhou; Yimeng Ren; Yujie Shi; Shijie Fan; Liyuan Zhao; Miaomiao Dong; Jing Li; Youyou Yang; Yanan Yu; Qingyu Zhao; Junmin Zhang; Chaohua Tang (Food Chemistry, 2024)

Dietary Macleaya cordata extract supplementation reduced high-fat–induced damage of antioxidant capacity and immune function, and alleviated the disorder of glycolipid metabolism in Marsupenaeus japonicus - Xin Zhang; Zhengxu Chen; Haitao Fan; Yanan Yin; Xuewei Feng; Xuming Guo; Lefei Jiao (Aquaculture International, 2024)

Time-varying ambient air pollution exposure is associated with gut microbiome variation in the first 2 years of life - Tianlai Qiu; Qingbo Fang; Xuqi Tian; Yanan Cao; Xiaoxiao Fan; Yanting Li; Yiming Tu; Linxia Liu; Zitong Chen; Yi Wei; Jinbing Bai; Jing Huang; et al. (Environmental Pollution, 2024)

Factors associated with self-rated mental health in mothers of children and adolescents with autism spectrum disorder - Yanan Zhao; Huiyun Fan; Rong Zhang; Xiaoying Zheng (Journal of Zhejiang University-SCIENCE B, 2024)

Occurrence and health risks of multiple emerging bisphenol S analogues in pregnant women from South China - Yanan Pan; Chunhong Jia; Zhenni Zhu; Zhiwen Su; Xin Wei; Renli Yin; Chongjian Ma; Wenwen Sun; Haijun Wu; Fan Wu; Adela Jing Li; Rongliang Qiu (Journal of Hazardous Materials, 2024)

Selenate simultaneously alleviated cadmium and arsenic accumulation in rice (Oryza sativa L.) via regulating transport genes - Siyu Huang; Qiqi Wang; Hao Qi; Zhe Liu; Yanjin Tao; Yu Fan; Qi Wang; Huafen Li; Yanan Wan (Environmental Pollution, 2024)

Exosomes derived from 3D-cultured MSCs alleviate knee osteoarthritis by promoting M2 macrophage polarization through miR-365a-5p and inhibiting TLR2/Myd88/NF-κB pathway - Lei Yan; Dijun Li; Songyan Li; Jiao Jiao Li; Guangyuan Du; Haifeng Liu; Jing Zhang; Xiaoke Li; Zijuan Fan; Jingwei Jiu; Ruoqi Li; Na Kong; et al. (Chemical Engineering Journal, 2024)

An energy-efficient cyclic amine system developed for carbon capture from both flue gas and air - Guanchu Lu; Zongyang Yue; Yanan Deng; Yuxiang Xue; Yi Huang; Xiaolei Zhang; Xianfeng Chen; Xianfeng Fan (Chemical Engineering Journal, 2024)

Unveiling the secrets of diatom-mediated calcification: Implications for the biological pump - Yiwen Pan; Yifan Li; Chen-Tung Arthur Chen; Zong-Pei Jiang; Wei-Jun Cai; Yunwen Shen; Zesheng Ding; Qixian Chen; Yanan Di; Wei Fan; Chenba Zhu; Ying Chen (Science China Earth Sciences, 2024)

Identification of potential natural product derivatives as CK2 inhibitors based on GA-MLR QSAR modeling, synthesis and biological evaluation - Yanan Xuan; Yue Zhou; Yue Yue; Na Zhang; Guohui Sun; Tengjiao Fan; Lijiao Zhao; Rugang Zhong (Medicinal Chemistry Research, 2024)

Co-ZIF-derived dual Co and Co3S4 nanoparticles encapsulated in N-doped carbon matrix for efficient photocatalytic CO2 reduction - Lili Huang; Shengpeng Mo; Xin Zhao; Jiangjing Zhou; Yanan Zhang; Xiaobin Zhou; Yinming Fan; Qinglin Xie; Daiqi Ye (Journal of Environmental Chemical Engineering, 2024)

Effects of microplastics on the structure and function of bacterial communities in sediments of a freshwater lake - Miaomiao Tao; Weibin Li; Xiaohong Zhou; Yanan Li; Haiya Song; Fan Wu (Chemosphere, 2024)

SERCA2 protects against cisplatin-induced damage of auditory cells: Possible relation with alleviation of ER stress - Yue Xu; Hao Zhao; Fan Wang; Shuai Xu; Chen Wang; Yanan Li; Yajie Wang; Huiming Nong; Junhong Zhang; Zhixin Cao; Chengfang Chen; Jianfeng Li (Toxicology and Applied Pharmacology, 2024)

Bioavailability transition path of phosphorus species during the sewage sludge incineration process - Qianqian Guo; Yanan Wang; Lingqin Zhao; Fan Yu; Zehuang Zhang; Nan Zhou; Long Jiao; Yanjun Hu (Environmental Research, 2024)

A mapping method for emission inventory and its application in air quality modeling - Jin Fan; Mengying Shen; Tingyu Yan; Kaicheng Zhang; Tongge Zhang; Chen Gong; Xinyun Tian; Yanan Shang; Xianyu Yang; Ping Shao; Wei Tang; Maoshan Li; et al. (Atmospheric Pollution Research, 2024)

Apoptosis-related prognostic biomarkers and potential targets for acute kidney injury based on machine learning algorithm and in vivo experiments - Hanyao Guo; Meixia Wang; Yanan Shang; Bo Zhang; Sidi Zhang; Xiaoyu Liu; Pengxiu Cao; Yumei Fan; Ke Tan (Apoptosis, 2024)

Natural compound Sanggenon C inhibits porcine reproductive and respiratory syndrome virus replication in piglets - Xiao Liu; Yinan Meng; Jianyu He; Xuelian Jiang; Shuangquan Zhang; Dan Wang; Yanan Zhu; Zifang Zheng; Yunpeng Fan; Yupeng Yin; Shuqi Xiao (Veterinary Microbiology, 2024)

Pig domestication and human subsistence at the early Neolithic site of Guanjia (6100–5500 BC), Central China - Yue You; Xianglong Chen; Anke Hein; Cunyu Qin; Yanan Zhao; Jiaxin Zhang; Tianyang Liu; Wenquan Fan; Guangkuo Yuan (Archaeological and Anthropological Sciences, 2024)

Newcastle disease virus activates the PI3K/AKT signaling pathway by targeting PHLPP2 degradation to delay cell apoptosis and promote viral replication - Lei Fan; Zhaoping Liang; Jinlian Ren; Yichun Chen; He Zhu; Yanan Chen; Bin Xiang; Qiuyan Lin; Chan Ding; Libin Chen; Tao Ren (Veterinary Microbiology, 2024)

Temporal dynamics of bacterial colonization on five types of microplastics in a freshwater lake - Haiya Song; Sisi Xiao; Xiaohong Zhou; Yanan Li; Miaomiao Tao; Fan Wu; Xiaohong Xu (Science of The Total Environment, 2024)

Hierarchically ordered microporous Ag2S QDs-CoOx/NC nanostructures for enhancing photocatalytic CO2 reduction to chemical fuels - Shengpeng Mo; Lili Huang; Xin Zhao; Jun Li; Xuegang Ding; Xiaobin Zhou; Yanan Zhang; Yinming Fan; Mingming Fu; Hongxiang Zhu; Qinglin Xie; Daiqi Ye (Fuel, 2024)

Interaction mechanism of pea proteins with selected pyrazine flavors: Differences in alkyl numbers and flavor concentration - Yanan Guo; Qi Gong; Fuwei Sun; Tianfu Cheng; Zhijun Fan; Zhaoxian Huang; Jun Liu; Zengwang Guo; Zhongjiang Wang (Food Hydrocolloids, 2024)

Inhibiting effect of 2-amino-2-methyl-1-propanol on gelatinous product formation in non-aqueous CO2 absorbents: Experimental study and molecular understanding - Chao Liu; Guohua Jing; Zongqiang Zhu; Yinming Fan; Shengpeng Mo; Yanan Zhang; Dunqiu Wang; Bihong Lv; Mingming Fu; Xiaobin Zhou (Chemical Engineering Journal, 2024)

Associations of nighttime light exposure during pregnancy with maternal and neonatal gut microbiota: A cohort study - Ni Wu; Yu Sun; Tianlai Qiu; Jun Liu; Yanan Cao; Tianzi Zang; Xiaoxiao Fan; Jinbing Bai; Jing Huang; Yanqun Liu (Science of The Total Environment, 2024)

Rapid and convenient synthesis of “green” ammonium-modified chitosan composite sponge with the existence of ascorbic acid for highly efficient removal of Congo red (CR) - Keyu Ren; Yanan Fan; Guozheng Xing; Mengge Zhai; Jie Sheng; Yishan Song (Carbohydrate Polymers, 2024)

Exploring recharge mechanisms of soil water in the thick unsaturated zone using water isotopes in the North China Plain - Huawu Wu; Fan Song; Leilei Min; Jing Li; Yanjun Shen; Yanan Huang; Hongxiang Fan; Jinzhao Liu; Congsheng Fu (CATENA, 2024)

Occurrence and correlation of microplastics and dibutyl phthalate in rivers from Pearl River Delta, China - Duojia Wang; Sabrina Yanan Jiang; Changchang Fan; Longshan Fu; Huada Daniel Ruan (Marine Pollution Bulletin, 2023)

Nexus between economic recovery, energy consumption, CO2 emission, and total natural resources rent - Kecai Fan; Mao Zheng; Yanan Shen; Fangfang Zhang (Resources Policy, 2023)

Transcriptome analysis revealed that short-term stress in Blattella germanica to β-cypermethrin can reshape the phenotype of resistance adaptation - Huiyuan Gao; Yanan Zang; Yuting Zhang; Haizheng Zhao; Wenxiao Ma; Xingyu Chen; Jingjing Wang; Dongqin Zhao; Xuejun Wang; Yanhong Huang; Fan Zhang (Pesticide Biochemistry and Physiology, 2023)

Effects of the tumor necrosis factor on hemocyte proliferation and bacterial infection in Chinese mitten crab (Eriocheir sinensis) - Yufan Bao; Guoqing Shen; Yanan Guo; Qun Wang; Xinpeng Fan; Weiwei Li (Fish & Shellfish Immunology, 2023)

Novel amino-modified bamboo-derived biochar-supported nano-zero-valent iron (AMBBC-nZVI) composite for efficient Cr(VI) removal from aqueous solution - Xiaobin Zhou; Yingxue Wang; Huili Liu; Yanan Zhang; Yinming Fan; Shengpeng Mo; Huaxia Li; Junyi Wang; Hua Lin (Environmental Science and Pollution Research, 2023)

New pathway of diatom-mediated calcification and its impact on the biological pump - Yiwen Pan; Yifan Li; Chen-Tung Arthur Chen; Zong-Pei Jiang; Wei-Jun Cai; Yunwen Shen; Zesheng Ding; Qixian Chen; Yanan Di; Wei Fan; Chenba Zhu; Nianzhi Jiao; et al. (Science Bulletin, 2023)

Exploring the contribution of environmental factors to evapotranspiration dynamics in the Three-River-Source region, China - Yan Zhao; Yanan Chen; Chaoyang Wu; Guo Li; Mingguo Ma; Lei Fan; Hui Zheng; Lisheng Song; Xuguang Tang (Journal of Hydrology, 2023)

Cumulative and lagged effects of varying-sized particulate matter exposure associates with toddlers’ gut microbiota - Tianlai Qiu; Tianzi Zang; Qingbo Fang; Zhihu Xu; Yanan Cao; Xiaoxiao Fan; Jun Liu; Xueer Zeng; Yanting Li; Yiming Tu; Guoxing Li; Jinbing Bai; et al. (Environmental Pollution, 2023)

3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase (HMGCR) protects hair cells from cisplatin‐induced ototoxicity in vitro: possible relation to the activities of p38 MAPK signaling pathway - Yanan Li; Huiming Yang; Huiming Nong; Fan Wang; Yajie Wang; Yue Xu; Junhong Zhang; Hao Zhao; Zhixin Cao; Qianqian Yang; Jianfeng Li (Archives of Toxicology, 2023)

Designing multi-layered MOF-on-MOF-transformed core double-shell FeSx@ZnS@CoSx heterojunction for enhanced CO2 photoreduction with water vapor - Lili Huang; Shengpeng Mo; Xin Zhao; Jiangjing Zhou; Xiaobin Zhou; Yanan Zhang; Mingming Fu; Yinming Fan; Qinglin Xie; Daiqi Ye; Yunfa Chen (Chemical Engineering Journal, 2023)

Formation and evolution mechanisms of a destructive-wind-producing thunderstorm in Shanghai - Yanan Liu; Fan Ping; Chenchen Ding; Xiaochen Zhang (Atmospheric Research, 2023)

Association between urinary 2-hydroxyethyl mercapturic acid and dyslexia among school-aged children - Haoxue Wang; Yanjian Wan; Qi Liu; Xinyan Xie; Kaiheng Zhu; Qi Jiang; Yanan Feng; Pei Xiao; Zhen Xiang; Quan Zhang; Yixi Fan; Xvfang Wu; et al. (Environmental Science and Pollution Research, 2023)

Novel strategy to improve the bioactivity and anti-hydrolysis ability of oat peptides via zinc ion-induced assembling - Junping Zhang; Yingxue Tang; Saiping Zhou; Xiaoyu Yin; Xueying Zhuang; Yanan Ren; Xiangning Chen; Junfeng Fan; Yanyan Zhang (Food Chemistry, 2023)

Does PM1 exposure during pregnancy impact the gut microbiota of mothers and neonates? - Yanan Cao; Tianzi Zang; Tianlai Qiu; Zhihu Xu; Xiangxu Chen; Xiaoxiao Fan; Qianping Zhang; Yingjuan Huang; Jun Liu; Ni Wu; Natalie Shen; Jinbing Bai; et al. (Environmental Research, 2023)

Application of fluorescence spectra and molecular weight analysis in the identification of algal organic matter-based disinfection by-product precursors - Xinyi Wang; Yunkun Qian; Yanan Chen; Fan Liu; Dong An; Guodong Yang; Ruihua Dai (Science of The Total Environment, 2023)

Study on the Classification Perception and Visibility Enhancement of Ship Navigation Environments in Foggy Conditions - Chiming Wang; Boyan Fan; Yanan Li; Jingjing Xiao; Lanxi Min; Jing Zhang; Jiuhu Chen; Zhong Lin; Sunxin Su; Rongjiong Wu; Shunzhi Zhu (Journal of Marine Science and Engineering, 2023)
Based on ship navigational requirements and safety in foggy conditions and with a particular emphasis on avoiding ship collisions and improving navigational abilities, we constructed a fog navigation dataset along with a new method for enhancing foggy images and perceived visibility using a discriminant deep learning architecture and the EfficientNet neural network by replacing the SE module and incorporating a convolution block attention module and focal loss function. The accuracy of our model exceeded 95%, which meets the needs of an intelligent ship navigation environment in foggy conditions. As part of our research, we also determined the best enhancement algorithm for each type of fog according to its classification.

Spatial Equity of Basic Education Resources and Coordinated Regional Development in Xinjiang, China - Tao Han; Jie Fan; Rui Guo; Yong Sun; Dong Chen; Baoying Liu; Yanan Lian (Chinese Geographical Science, 2023)

The Paleoenvironment and Mechanisms of Organic Matter Enrichment of Shale in the Permian Taiyuan and Shanxi Formations in the Southern North China Basin - Yanan Wang; Xiulei Cheng; Kai Fan; Zhipeng Huo; Lin Wei (Journal of Marine Science and Engineering, 2023)
The organic-rich shale of the Permian Taiyuan Formation (TYF) and Shanxi Formation (SXF) in the Southern North China Basin (SNCB) is considered a potential shale gas source. The shale was formed in a marine-continental transitional sedimentary environment, which has rarely been studied, with the enrichment mechanisms of organic matter (OM) remaining unclear. This study investigated the controlling factors and enrichment mechanisms of OM by analyzing the total organic carbon (TOC) content, paleoclimate, paleoproductivity, sedimentation rate, redox, and paleosalinity. The TOC of the TYF ranged from 0.92 to 7.43 wt.%, with an average of 2.48 wt.%, which was higher than that of the SXF (TOC = 0.36–5.1 wt.%, average of 1.68 wt.%). These geochemical indices suggest that both the TYF and SXF were deposited in warm and humid paleoclimates, with relatively high biological productivity and sedimentation rates. During the deposition process, the TYF experienced frequent transgression and regression events, leading to an enhancement of water reducibility, a relatively high sedimentation rate, reduced OM oxidation, and rapid deposition of OM, which were conducive to the preservation of OM. Moreover, a high biological productivity increased respiratory oxygen consumption in the water column, which could lead to OM accumulation. However, the regression event experienced by the SXF reduced the paleoproductivity and sedimentation rate and increased water oxidation, leading to a decrease in OM. The main controlling factors for the enrichment of OM in the TYF and SXF were the sedimentation rate, paleoproductivity, and redox conditions, thus establishing the enrichment models for OM in the TYF and SXF. This study is conducive to understanding shale enrichment mechanisms and guiding shale gas exploration.

Hollow cavity engineering of MOFs-derived hierarchical MnOx structure for highly efficient photothermal degradation of ethyl acetate under light irradiation - Jun Li; Shengpeng Mo; Xuegang Ding; Lili Huang; Xiaobin Zhou; Yinming Fan; Yanan Zhang; Mingming Fu; Qinglin Xie; Daiqi Ye (Chemical Engineering Journal, 2023)

DJ-1 Protects auditory cells from cisplatin-induced ototoxicity via regulating apoptosis and autophagy - Yajie Wang; Hao Zhao; Fan Wang; Huiming Nong; Yanan Li; Yue Xu; Mingqiang He; Jianfeng Li (Toxicology Letters, 2023)

Transition of cooking fuel types and mortality risk in China, 1991–2015 - Fan Pu; Chenxi Li; Xinrui Zhang; Xingqi Cao; Zhenqing Yang; Yingying Hu; Xiaolin Xu; Yanan Ma; Kejia Hu; Zuyun Liu (Science of The Total Environment, 2023)

Spatial characterization of HCHO and reapportionment of its secondary sources considering photochemical loss in Taiyuan, China - Jingya Hua; Yang Cui; Lili Guo; Hongyan Li; Jie Fan; Yanan Li; Yonghong Wang; Kankan Liu; Qiusheng He; Xinming Wang (Science of The Total Environment, 2023)

Association of solid fuel use with a risk score capturing dementia risk among middle-aged and older adults: A prospective cohort study - Fan Pu; Yingying Hu; Chenxi Li; Xingqi Cao; Zhenqing Yang; Yi Liu; Jingyun Zhang; Xueqin Li; Yongli Yang; Wei Wang; Xiaoting Liu; Kejia Hu; et al. (Environmental Research, 2023)

Significant impact of VOCs emission from coking and coal/biomass combustion on O3 and SOA formation in taiyuan, China - Yu Wang; Yang Cui; Qiusheng He; Jie Fan; Yanan Li; KanKan Liu; Lili Guo; Xinming Wang (Atmospheric Pollution Research, 2023)

Impacts of mowing and N addition on soil organic phosphorus mineralization rates in a semi-natural grassland in Northeast China - Haiying Cui; Mingcai Fan; Yunbo Wang; Xiaochong Zhang; Wanling Xu; Yanan Li; Wenzheng Song; Jian-Ying Ma; Wei Sun (Plant and Soil, 2023)

Quantitative assessment of the habitat quality dynamics in Yellow River Basin, China - Yanan Song; Meng Wang; Xiaofang Sun; Zemeng Fan (Environmental Monitoring and Assessment, 2021)

Investigation of the “dust reservoir effect” of the Tarim Basin using WRF-GOCART model - Jin Fan; Yanan Shang; Qiang Chen; Shigong Wang; Xiaoling Zhang; Lei Zhang; Ying Zhang; Xuanye Xu; Peiya Jiang (Arabian Journal of Geosciences, 2020)

Adoptive transfer of IFN-γ-induced M-MDSCs promotes immune tolerance to allografts through iNOS pathway - Fan Yang; Yang Li; Weilong Zou; Yanan Xu; Hao Wang; Wei Wang; Yong Zhao (Inflammation Research, 2019)

Effective detection of Lily Symptomless Virus using the reverse transcription loop–mediated isothermal amplification method - Xiao Zhao; Yanan Du; Yongchun Zhang; Jieling Liang; Youming Cai; Yan Xu; Xiaorui Fan; Wenjing Wu; Qi Zhang; Xiaoxia Zhang; Dan Yang; Ziping Zhu; et al. (Australasian Plant Pathology, 2019)

Correction to: Identification of β‑carboline and canthinone alkaloids as anti‑inflammatory agents but with different inhibitory profile on the expression of iNOS and COX‑2 in lipopolysaccharide‑activated RAW 264.7 macrophages - Pan Liu; Huixiang Li; Ruiling Luan; Guiyan Huang; Yanan Liu; Mengdi Wang; Qiuli Chao; Liying Wang; Danna Li; Huaying Fan; Daquan Chen; Linyu Li; et al. (Journal of Natural Medicines, 2019)

Identification of β-carboline and canthinone alkaloids as anti-inflammatory agents but with different inhibitory profile on the expression of iNOS and COX-2 in lipopolysaccharide-activated RAW 264.7 macrophages - Pan Liu; Huixiang Li; Ruiling Luan; Guiyan Huang; Yanan Liu; Mengdi Wang; Qiuli Chao; Liying Wang; Danna Li; Huaying Fan; Daquan Chen; Linyu Li; et al. (Journal of Natural Medicines, 2019)

Spatio-temporal analysis of the geographical centroids for three major crops in China from 1949 to 2014 - Lingling Fan; Shefang Liang; Hao Chen; Yanan Hu; Xiaofei Zhang; Zhenhuan Liu; Wenbin Wu; Peng Yang (Journal of Geographical Sciences, 2018)

Rapid visual detection of lily mottle virus using a loop-mediated isothermal amplification method - Binan Zhao; Dan Yang; Yongchun Zhang; Yan Xu; Xiao Zhao; Jieling Liang; Xiaorui Fan; Yanan Du; Ziping Zhu; Bin Shi; Qi Zhang; Xiaoxia Zhang; et al. (Archives of Virology, 2018)

Research progress in artificial upwelling and its potential environmental effects - YiWen Pan; Wei Fan; DaHai Zhang; JiaWang Chen; HaoCai Huang; ShuXia Liu; ZongPei Jiang; YaNan Di; MengMeng Tong; Ying Chen (Science China Earth Sciences, 2016)

Dystrophin Involved in the Susceptibility of Slow Muscles to Hindlimb Unloading via Concomitant Activation of TGF-β1/Smad3 Signaling and Ubiquitin–Proteasome Degradation in Mice - Peng Zhang; Wenjiong Li; Hongju Liu; Jinglong Li; Jing Wang; Yanan Li; Xiaoping Chen; Zhong Yang; Ming Fan (Cell Biochemistry and Biophysics, 2014)

Influence of Cosubstrates on Iopromide Degradation by Pseudomonas sp. I-24 - Bingjie Xu; Pin Gao; Zhenhong Liu; Gang Xue; Yanan Liu; Fan Wu (Water, Air, & Soil Pollution, 2014)

Primary dolostone related to the Cretaceous lacustrine hydrothermal sedimentation in Qingxi sag, Jiuquan Basin on the northern Tibetan Plateau - HuaGuo Wen; RongCai Zheng; Hairuo Qing; MingTao Fan; YanAn Li; BoShi Gong (Science China Earth Sciences, 2013)